Problem Faced by Teachers and Students in Implementing Authentic Assessment for Reading Literacy in Junior High Schools in Padang - Tasia Putri Iglen; Yetti Zainil (Journal of English Language Teaching, 2022)
This research focus on problem in assessment for reading literacy to promote high order thinking, critical thinking, and argumentative thinking skills. This research is descriptive research. It required observing and describing a subject’s behavior in addition to using written information from teachers obtain through observation, interview, and questionnaire. Students are also given questionnaire to complete, in order to collect data from them. The subjects of this research were 5 teachers and 78 students from 2 schools selected. The techniques of data collection were analyzing observation, interview, and questionnaire. The findings of this research from all questions, it was found that the students had problems in the aspect of reading literacy competence, but from the results of the questionnaire to the teacher, they had no difficulty in making tests based on the aspects of reading literacy competence. in other finding, students have difficulty answering questions based on the text, however teachers find problems in creating the test based on kinds of text.